Resurgence of measles infection among children: findings from a surveillance-based population study - Idayu Badilla Idris; Intan Azura Mhd. Din; Norfazilah Ahmad; Na’eemah Zaini (Paediatrica Indonesiana, 2023)
Background There has been a resurgence of measles infection in countries with high vaccination rates, including Malaysia. Understanding the geographical variation in measles resurgence and associated factors is important for measles prevention and control programs, especially where local information is scarce. Objective To determine the incidence of laboratory-confirmed measles infection and associated factors in the state of Melaka, in the southern region of Malaysia. Methods We obtained measles surveillance data for 4 years (January 2015 to December 2018) from the e-Measles national database. A comparative cross-sectional study was carried out on these data involving children who had been selected through convenience sampling. Results A total of 130 laboratory-confirmed measles cases and 213 non-measles cases were included in the study. Among the laboratory-confirmed cases, 56 (43.1%) had not been vaccinated against measles virus. Thirty-eight cases (51.4%) had received at least one dose of measles vaccine, while 36 cases (48.6%) had completed two doses of measles vaccination. There was a higher risk of contracting laboratory-confirmed measles among unvaccinated children (OR 19.39, 95%CI 8.82 to 42.6, P<0.001) and children aged 8–18 years (OR 0.40, 95% CI 0.21 to 0.76, P=0.005) Conclusion Unvaccinated children and children aged 8–18 years have a higher risk of contracting laboratory-confirmed measles. The policy on routine immunization should be strengthened, the vaccine should be accessible to all children, and all children and adolescents should be given booster vaccinations.